Identification of plant parasitic nematodes in the germplasm bank of yellow passion fruit (passiflora edulis f. flavicarpa degener) in colombia (2012)
Plant parasitic nematodes are one of the major constraints in tropical fruit causing great economic losses by reducing yields. In Colombia there is not information dealing with the production systems about these parasites affecting passion fruit cultivation so, it is necessary to generate information for management strategies. The aim of this study was to identify and quantify plant parasitic nematodes present in the National yellow passion fruit Collection consisting of 28 accessions from different origin and established in the farm Luker in Palestina (Caldas), Colombia. Sample collection was carried out in the root area of each plant at a depth of 60 cm in each accession. Three samples of 100 g of functional root system and 100 g of soil were taken. The extraction of root and soil nematodes was based on the flotation principle of nematodes in sugar. For data an univariate analysis with the estimated average, the coefficient of variation, analysis of variance and Tukey test at 5%, to establish the differences among accessions was performed. Results showed seven kinds of soil and root phytonematodes: Helicotylenchus, Rotylenchulus, Radopholus, Meloidogyne, Tylenchus, Aphelenchoides and Trichodorus. The species most frequently found in root and soil of accessions were Helicotylenchus dihystera, Rotylenchulus reniformis and Radopholus similis with 100, 75 and 61%, respectively. Results showed 11, 8 y 16 accessions without parasitism of the genera Radopholus, Rotylenchulus and Meloidogyne, respectively. Among these, accession AntFla03 and CauFla01 were outstanding due to their agronomic characteristics which constitute a gene pool for breeding programs in search for phytoparasitic nematode resistance or tolerance that involve hybridization or grafting.